2005
DOI: 10.1590/s0100-879x2005000500010
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anaerobic threshold using heart rate response during dynamic exercise

Abstract: The objective of the present study was to characterize the heart rate (HR) patterns of healthy males using the autoregressive integrated moving average (ARIMA) model over a power range assumed to correspond to the anaerobic threshold (AT) during discontinuous dynamic exercise tests (DDET). Nine young (22.3 ± 1.57 years) and 9 middle-aged (MA) volunteers (43.2 ± 3.53 years) performed three DDET on a cycle ergometer. Protocol I: DDET in steps with progressive power increases of 10 W; protocol II: DDET using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
2
10
0
4
Order By: Relevance
“…Thus, our findings showed that the mathematical model was adequate for AT determination in sedentary healthy women. Other studies from our laboratory found that the ventilatory AT (gold standard method) was very close to the AT determined by the autoregressive integrated moving average model applied to middle-aged healthy men (10).…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…Thus, our findings showed that the mathematical model was adequate for AT determination in sedentary healthy women. Other studies from our laboratory found that the ventilatory AT (gold standard method) was very close to the AT determined by the autoregressive integrated moving average model applied to middle-aged healthy men (10).…”
Section: Resultssupporting
confidence: 57%
“…Some studies (8,9) have used the graphic visual method for the estimate of the disproportionate increase in ventilatory and metabolic variables, during the incremental dynamic exercise, as a gold standard for the quantification of AT. Additionally, other investigators have identified AT by analysis of heart rate (HR) (3,(10)(11)(12)(13) and of its variability (14), as well as by surface electromyography analysis (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent increments corresponded to 10% of maximal power reached in the clinical exercise test. The TAv was visually identified when the rate of CO 2 release presented non-linear increment concerning the oxygen consumption (VO 2 ) 1,12 . The oxygen consumption (O 2 ) was picked breath-after-breath through a gas analyzer and metabolic measures (MMC Horizontal System, Sensormedics, Yorba Linda, CA, USA) and their values were expressed in means at every 15s.…”
Section: Cardiopulmonary Exercise Test (Cpet)mentioning
confidence: 99%
“…Nevertheless, one cannot exclude the possibility of sympathetic contribution in this period. After the 60º second of moderate or intense exercise, slow HR increment is observed as consequence of the sympathetic contribution on the sinusal nodule 6,12 . Such behavior, represented by the variables of the 60-240º second interval (β, I and ∆), has its magnitude temporarily correlated with alterations in the blood lactate concentration 7,[26][27][28] .…”
Section: Cpetmentioning
confidence: 99%